2018
DOI: 10.1371/journal.pone.0204436
|View full text |Cite
|
Sign up to set email alerts
|

Survival and years of life lost in various aetiologies of dementia, mild cognitive impairment (MCI) and subjective cognitive decline (SCD) in Norway

Abstract: IntroductionAlzheimer’s disease patients are reported to have higher survival rate compared to patients with vascular dementia or dementia with Lewy bodies. There is a paucity of studies investigating survival including persons with cognitive decline and dementia of various aetiologies.ObjectivesWe aimed to compare survival for patients with subjective cognitive decline, mild cognitive impairment, Alzheimer’s disease, vascular dementia, mixed Alzheimer’s/vascular dementia, dementia with Lewy bodies/Parkinson’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 38 publications
4
52
1
Order By: Relevance
“…The mortality risks of our patients with dementia were comparable with the Swedish Dementia Registry (114 deaths/1000 person‐years), and our findings support the notion that old age and male gender are associated with poor survival among patients with cognitive complaints . Survival varied across dementia types and was found to be longer in AD than VaD, DLB, PDD, or mixed dementia (AD with VaD) . In our study, the survival difference among three diagnostic categories by the Kaplan‐Meier method disappeared after adjusting for age, gender, and baseline cognitive function in the Cox regression models.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mortality risks of our patients with dementia were comparable with the Swedish Dementia Registry (114 deaths/1000 person‐years), and our findings support the notion that old age and male gender are associated with poor survival among patients with cognitive complaints . Survival varied across dementia types and was found to be longer in AD than VaD, DLB, PDD, or mixed dementia (AD with VaD) . In our study, the survival difference among three diagnostic categories by the Kaplan‐Meier method disappeared after adjusting for age, gender, and baseline cognitive function in the Cox regression models.…”
Section: Discussionsupporting
confidence: 86%
“…8,11,24,25 Survival varied across dementia types and was found to be longer in AD than VaD, DLB, PDD, or mixed dementia (AD with VaD). 11,26 In our study, the survival difference among three diagnostic categories by the Kaplan-Meier method disappeared after adjusting for age, gender, and baseline cognitive function in the Cox regression models. Baseline MMSE scores, especially when lower than 17, were predictive of higher mortality risks.…”
Section: Discussionmentioning
confidence: 52%
“…Average post-diagnosis survival time for women (4.6–5.1 years) is longer than for men (4.1–4.3 years) ( 38 , 39 , 41 ), while life expectancy following diagnosis is determined individually by a number of predictors, e.g., age, sex, increased comorbidity, and type of dementia ( 42 44 ). People with vascular dementia or Lewy bodies have a shorter survival time than people with Alzheimer’s disease ( 45 , 46 ).…”
Section: Special Prerequisites Of Palliative Care In Advanced Dementimentioning
confidence: 99%
“…It is suggested that subjective cognitive impairment, which is recognised as a potential indicator for cognitive decline, is linked to all-cause mortality [8]. However, some studies argue that subjective cognitive decline does not predict mortality when objective cognitive deficits are controlled [9][10][11]. As scientists put it, complaints about cognitive abilities do not ultimately lead to cognitive impairment in all cases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the link between cognitive function and mortality is not clear. Previous studies ascertained different links between cognitive decline and survival [9]. There also might be a difference in association according to the cause of death [19].…”
Section: Introductionmentioning
confidence: 99%